Evaluation of autologous periodontal stem cells niche in the treatment of periodontal intrabony defects: A split-mouth randomized controlled trial - Hungyo Chanreiphy; Vineeta Gupta; Kharidhi Laxman Vandana; Varsha Goswami; Bhumika Jhawar; V. Vinitha (Journal of Indian Society of Periodontology)
Background: Regeneration of the lost periodontium requires an abundant supply of the desired cell. Stem cells can provide progenitor cells at the target location; however stem cell therapy is technique sensitive. Thus, using periodontal ligament stem cells (PDLSCs) of an extracted tooth can act as a feasible and accessible alternative to an otherwise expensive elaborate process. Thus, the aim of this study was to evaluate the effects of direct transplantation of autologous PDLSC niche in two-walled or three-walled intrabony defects. Materials and Methods: A total of 16 patients having bilateral intrabony defects (total 32 sites) were recruited for the study. The socioeconomic status was also taken into consideration. After randomization, the sites were treated with either open flap debridement alone (control group) or open flap debridement followed by direct transplantation of autologous periodontal ligament stem cells niche (APDLSc Ni-test group). For each surgical site, clinical parameters were evaluated at baseline, 3, 6, and 9 months. Radiographic assessment was made at baseline, 6, and 9 months. Results: Both the groups have shown improvement from baseline to 9 months in clinical and radiological parameters, which was statistically significant. The intergroup comparison has shown a nonsignificant difference in favor of the APDLSc Ni group. However, bone fill was better with A PDLSc Ni than open flap debridement alone. Conclusion: The result of the present study concluded that treatment of intrabony defect by direct transplantation of autologous periodontal ligament stem cells niche was beneficial and can be used in a simple clinical setup.